Perancangan Ulang UI/UX Website Learning Management System Startup XYZ Dengan Metode User-Centered Design - Sabrina, Venira Citra; Wibowo, Nur Cahyo; Wati, Seftin Fitri Ana (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
XYZ is an education technology startup providing IT bootcamps through a Learning Management System (LMS) platform. The platform faces a primary challenge: users' lack of understanding of features such as reminders and history, as well as the need for monitoring learning progress features. User satisfaction testing yielded low results. This study aims to redesign the XYZ LMS website with a focus on UI/UX to enhance accessibility and learning satisfaction, utilizing User-Centered Design (UCD) methodology and usability testing. The research resulted in a prototype UI/UX design for the LMS, with significant improvement observed in the System Usability Scale (SUS) score, which increased to 91.42, and user performance reaching 93.01% in usability testing. These outcomes indicate the success of the new design implementation